Evaluation of High Standardized Ileal Digestible Tryptophan:Lysine Ratios with Ractopamine HCl on Growth and Carcass Performance of Pigs from 240 to 295 lb - J. Soto; M. D. Tokach; K. J. Touchette; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 935 pigs (PIC 1050 × 337, initially 237.2 lb BW) were used in a 22-d trial to determine the effects of feeding high levels of standardized ileal digestible (SID) Trp:Lys ratio in diets with ractopamine HCl (RAC, Paylean, Elanco Animal Health, Greenfield, IN) on growth and carcass performance of finishing pigs. Pens of 23 or 24 pigs were allotted by BW and randomly assigned to 1 of 5 dietary treatments with 8 replications per treatment. The dietary treatments included 5 SID Trp:Lys ratios (20, 22, 24, 26, and 28% of Lys). All diets were formulated to 0.90% SID Lys and contained 10 ppm ractopamine. At d 22, pigs were transported to a packing plant for processing and carcass data collection. For overall growth performance, increasing SID Trp:Lys increased (linear, P<0.05) ADFI and SID Trp g/kg gain. However, there was no evidence for treatment differences for ADG or F/G. For carcass characteristics, there was no evidence for treatment differences for HCW, carcass yield, backfat loin depth, lean, carcass ADG, or carcass feed efficiency. In summary, increasing SID Trp:Lys increased ADFI and SID Trp g/kg gain, however, there was no evidence for treatment differences for other growth or carcass parameters measured.
Keywords: amino acid; growth; tryptophan; finishing pigs